Paciente masculino de 52 años con diabetes mellitus tipo ii y obesidad grado ii - Chicaiza Cevallos, Néstor Dayan (2019)
DC is a 52-year-old male patient, owner of a private personal security company in Babahoyo, has 1 son, married marital status comes from diabetic parents, anthropometric measurements are taken, resulting in weight 98 kg and measures 167cm , temperature 36.5 degrees, go to the office for having fasting blood glucose of 160mg / dl. The corresponding tests were carried out confirming the diagnosis of type II diabetes mellitus, it has a glycosylated hemoglobin of 8.56% total cholesterol 192mg / dl, triglycerides 136 mg / dl, hemoglobin 14.3 g / dl, albumin 4 g / dl, Hematocrit 48%. Complete blood count within normal parameters. He reports that he does not like fruits, consumes alcohol once a week, does not perform any type of physical activity. The doctor prescribed 500mg xr glucofaje 1 at night and is referred to the nutritionist.